Penilaian Hasil Dipstik Urine (Nitrit Dan Leukosit Esterase) Sebagai Prediktor Bakteriuria - Parwati, Putu Ayu; Cahyani, Anak Agung Ayu Eka (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Bacteriuria is the leading indicator of Urinary Tract Infection (UTI), which is detected through urine culture examination. Significant bacteriuria indicates the growth of microorganisms as much as ≥ 100,000 cfu/ml in urine culture. There are drawbacks to this examination that requires a screening test with a short time and lower cost. This study aimed to determine differences in the results of nitrite and leukocyte esterase examination using a urine dipstick with urine culture as a predictor of bacteriuria. The type of research used is analytic with an experimental approach. The sample used in this study was ten samples of urine. Based on the bivariate analysis results, the p-value was 0.541, which means that there was no difference in the results of leukocyte esterase and urine culture. This indicates the presence of leukocytes in the urine can be an indication of bacteriuria. The results for the nitrite examination obtained a p-value of 0.000, which means there is a difference between the results of the nitrite examination and the results of the urine culture. This shows that the presence of nitrites in the urine cannot indicate of bacteriuria. However the data on the sensitivity and specificity of dipstick examination are still low for leukocyte esterase and urine nitrite tests. However, urine dipstick examination to detect bacteriuria and UTI is still an option for faster screening. Keywords       : leukocyte esterase, nitrites, urine culture